Phenomenon of Demikhov. At N.V. Sklifosovsky Institute (1960–1986). V.P. Demikhov and his experiments in the field of organ transplantation in 1971–1972 - S. P. Glyantsev; Yu. A. Shabunts (Трансплантология (Москва))
Having reviewed the archival documents, we enlightened the results of research performed by V.P. Demikhov and the employees of the Organ Transplantation Laboratory at the N.V. Sklifosovsky Research Institute, as well as V.P. Demikhov’s life and work in 1971–1972. During those years he continued to conduct the research required, as he believed, for practical healthcare. In 1971, together with M.M. Razgulov, he proposed a method for connecting blood vessels, a method for transplanting an upper limb together with a scapula, repeated experiments previously carried out on dogs, on human corpses (revitalization of a cadaveric heart, monitoring its activity using electrocardiography, implanting an additional heart into the cadaver’s chest in order to implement the technique in clinic for the treatment of heart failure), presented the results of his research at the X International Congress on Cardiovascular Diseases. We have also shown that in 1971–1972 V.P. Demikhov performed 76 experimental interventions, most of which were aimed at the development of a technique for transplanting an isolated cardiopulmonary complex and heart, as well as the technique for their revitalization. It should be noted that all the methods of organ transplantation developed by him were intended for implementation in clinic. However, no method was introduced into clinic during his lifetime. The fact is that the studies of V.P. Demikhov in the field of organ transplantation could not be adequately supplied from the material, technical and economic point, since they did not correspond to the main trends of the scientific and practical activities of the N.V. Sklifosovsky Institute – to improve the organizing system of rendering an emergency and urgent care to the population of Moscow in acute diseases and injuries.